Different cognitive abilities displayed by action video gamers and non-gamers. (November 2018) - Kowal, Magdalena; Toth, Adam J.; Exton, Chris; Campbell, Mark J.
Abstract: Playing action video games requires players to develop a cognitive profile that allows them to rapidly monitor and react to fast moving visual and auditory stimuli, and to inhibit erroneous actions. This study investigated whether experience with action videogames is associated with an advantage on standardized cognitive tasks. Specifically, we investigated whether individuals who played action video games demonstrated enhanced cognitive processing speed, task-switching and inhibitive abilities. First person shooter (FPS) and Massive online battle arena (MOBA) experienced video game players (AVGPs) and individuals with little to no videogame experience (NVGPs) performed both a Stroop test and a Trail-Making test (TMT A&B). Results showed that on the Stroop test, AVGPs responded significantly faster than NVGPs but made significantly more errors. Alternatively, on the TMT test AVGPs displayed faster reaction times while error rates did not differ compared to NVGPs. Our findings suggest that while AVGPs may possess enhanced processing speed and task-switching ability, AVGPs adopt a strategy that favours speed over accuracy on a task evaluating cognitive inhibition ability. Our data corroborate and bolster previous findings demonstrating a different cognitive profile for individuals that specifically play action video games. Highlights: For Stroop, AVGPs responded faster than NVGPs but made significantly more errors. For TMT AVGPs displayed faster RTs while error rates did not differ compared to NVGPs. AVGPs display more efficient processing speed and task-switching ability. AVGPs adopt a strategy favouring speed over accuracy on a cognitive inhibition task. Our data corroborate previous findings of a different cognitive profile for AVGPs.